Survival benefit of hepatic resection for hepatocellular carcinoma beyond the Barcelona Clinic Liver Cancer classification - Furukawa, Kenei; Shiba, Hiroaki; Horiuchi, Takashi; Shirai, Yoshihiro; Haruki, Koichiro; Fujiwara, Yuki; Sakamoto, Taro; Gocho, Takeshi; Yanaga, Katsuhiko (Journal of Hepato-Biliary-Pancreatic Sciences, 2017)
Background The Barcelona Clinic Liver Cancer (BCLC) classification is the most widely used staging system for hepatocellular carcinoma (HCC), but its prognostic ability in patients after resection has not been yet validated. The aim of this study was to evaluate the BCLC classification among patients after resection. Methods The subjects were 196 patients who underwent hepatic resection for HCC between April 2003 and December 2014 at Jikei University Hospital. All patients were classified into a tumor stage according to the BCLC classification. Overall survival rate was calculated according to stages defined by the BCLC classification. Results Overall survival rates at 1, 3 and 5‐year were 100%, 95.2% and 95.2% in BCLC 0, 96.7%, 90.0% and 78.4% in BCLC A solitary, 86.2%, 86.2% and 86.2% in BCLC A multiple, 100.0%, 78.8% and 78.8% in BCLC B and 86.5%, 63.3% and 57.6% in BCLC C, respectively. Postoperative complications and mortality rates in relation to BCLC stage were comparable. Conclusion The BCLC treatment algorithm should consider the role of resection also for multiple early, intermediate and advanced stages. HighlightFurukawa and colleagues evaluated the role of hepatic resection for hepatocellular carcinoma in relation to the Barcelona Clinic Liver Cancer (BCLC) classification. Hepatic resection provided good overall survival for each BCLC stage, suggesting that the BCLC treatment algorithm should consider the role of resection in each of the BCLC stages.